The role of interleukin-17 in the pathogenesis of systemic sclerosis: Pro-fibrotic or anti-fibrotic?. Issue 3 (October 2021) - Bellando-Randone, Silvia; Della-Torre, Emanuel; Balanescu, Andra
Systemic sclerosis is characterized by widespread fibrosis of the skin and internal organs, vascular impairment, and dysregulation of innate and adaptive immune system. Growing evidence indicates that T-cell proliferation and cytokine secretion play a major role in the initiation of systemic sclerosis, but the role of T helper 17 cells and of interleukin-17 cytokines in the development and progression of the disease remains controversial. In particular, an equally distributed body of literature supports both pro-fibrotic and anti-fibrotic effects of interleukin-17, suggesting a complex and nuanced role of this cytokine in systemic sclerosis pathogenesis that may vary depending on disease stage, target cells in affected organs, and inflammatory milieu. Although interleukin-17 already represents an established therapeutic target for several immune-mediated inflammatory diseases, more robust experimental evidence is required to clarify whether it may become an attractive therapeutic target for systemic sclerosis as well.